Deliverable D9.1- report on generic sops- Mandatory, recommended requirements, acceptance criteria, tolerance limits- Deliverable of TDS Project Work Package - Pité, Marina (2014)
Grant Agreement number 289108 Collaborative Project FP7-KBBE-2011-5